EFFECTIVENESS OF DIETARY APPROACHES TO STOP HYPERTENSION (DASH) ON BLOOD PRESSURE AND BLOOD GLUCOSE LEVELS AMONG PEOPLE WITH HYPERTENSION AND DIABETES MELLITUS - Vidhiastutik, Yusiana; Indasah; Widyowati, Agustin (Universitas Nahdlatul Ulama Surabaya, 2025)
Introduction: Hypertension and diabetes mellitus are degenerative diseases that increase due to risk factors such as obesity, aging, poor diet, and unhealthy lifestyle. Objective: The research was to assess the effectiveness of the DASH diet in reducing blood pressure and blood glucose levels in hypertensive and diabetic patients. Methods: A single-factor quasi-experimental study with a randomized pretest-posttest comparison group design was conducted on 36 respondents selected through simple random sampling from 305 Posbindu residents in Setonorejo Village. Data collection involved observation sheets, sphygmomanometers, glucose test kits, and the DASH diet SOP. The Wilcoxon Signed-Rank Test and the Kruskal-Wallis Test were used for data analysis. Results: The DASH diet significantly reduced systolic blood pressure (p = 0.006) and blood glucose levels (p = 0.008). However, only the 2600-calorie DASH diet significantly impacted diastolic blood pressure (p = 0.025), while 1600 and 2000-calorie diets did not (p = 0.083; p = 0.059). The Kruskal-Wallis test showed no significant differences between diet groups for systolic blood pressure (p = 0.319), diastolic blood pressure (p = 0.618), and blood glucose levels (p = 0.128). Conclusions: The DASH diet effectively lowers systolic blood pressure and blood glucose levels, suggesting its potential as a non-pharmacological strategy for managing hypertension and diabetes mellitus.